Safety Risk Management in Dam Construction Projects: Literature Review - Aulia, Dinal; marifah, lusi; Yurrazak, Ikbal; Purba, Humiras Hardi (Journal of Industrial and Engineering System, 2021)
Safety risk assessment in dams is a traditional and modern approach to the engineering process of dams on safety systems so as to produce a design history that has a good overall record and integrity. With this approach for both old and new dams, this safety risk assessment aims to determine whether the risk the hazard can be tolerated or not, if it cannot be tolerated then there must be a solution for action to reduce the risk of danger so that the safety of the dam can be obtained. The existing risk assessment can be used as the basis for the construction of the dam to its maintenance, in this study discussed risk assessment safety on dams located in several countries such as in Asia, Europe and America. The methods implemented include the preparation of safety risks, risk analysis, risk evaluation and safety risk management. Based on research results The main risk factor that causes safety responsibilities is the Contractor's responsibility, namely the Non-technical project factor (40.54%), the 2nd rank is the Undecided Responsibility due to internal technical factors (35.13%), the 3rd rank is the technical project factor namely Contractor's Responsibility (10.8%), Rank 4 is external technical factor and external non-technical factor, the last risk factor is internal non-technical factor (2.7%) namely Joint Responsibility. Keywords : Risk safety management, risk assessment, risk analysis, risk evaluation, dam project